Hubungan Konsep Diri Dengan Kesejahteraan Psikologis Pada Pasien Hiv/Aids Di Lembaga Cahaya Prolink Kabupaten Pobolinggo - Deli Indah Lestari; Rizka Yunita; Nafolion Nur Rahmat (Pusat riset dan Inovasi Nasional, 2023)
Human Immunodeficiency Virus/Acquired Immune Deficiency Syndrome (HIV/AIDS) can attack the human immune system. HIV/AIDS patients experience symptoms both physically, psychologically, socially. This condition is related to the occurrence of self-concept of HIV/AIDS patients who have a negative view of themselves. HIV/AIDS patients have difficulty managing themselves because they lose hope so that it can affect their psychological well-being. The purpose of this study was to analyze the relationship between self-concept and psychological well-being in HIV/AIDS patients This research method uses correlational analytic with cross sectional approach. The population was 50 respondents and the research sample was 50 respondents HIV/AIDS patients at the Cahaya Prolink Institute, Probolinggo regency using total sampling. The research instrument used a Robson Self Concept Questionnaire to measure self-concept, Riff Psychological well Being to measure psychological well-being, both questionnaires have been tested for validity and reliability. Then analyzed using the Spearman Rank test. The results of this study showed that 26 respondents (52.0%) or the majority of HIV/AIDS patients had low self-concept, and 25 respondents (50.0%) of HIV/AIDS patients had low psychological well-being. Based on the results of the Spearman Rank statistical test, it can be said that there is a correlation between self-concept and psychological well-being, pvalue=0.001 with a significant level of 0.05 (p≤0.05). HIV/AIDS patients experience low self-concept problems such as feeling humiliated, worried, having no purpose in life. HIV/AIDS patients experience low psychological well-being such as feeling no future, down, frustrated, worried, disappointed. It can be concluded that there is a relationship between self-concept and psychological well-being in HIV/AIDS patients. It is hoped that HIV/AIDS patients have a good picture so that they can accept themselves, have hope to continue life.